Pim1 knockout alleviates sarcopenia in aging mice via reducing adipogenic differentiation of PDGFRα+ mesenchymal progenitors. Issue 6 (25th August 2021) - Shang, Guo‐kai; Han, Lu; Wang, Zhi‐hao; Song, Ming; Wang, Di; Tan, Yan‐min; Li, Yi‐hui; Li, Yu‐lin; Zhang, Wei; Zhong, Ming
Abstract: Background: Sarcopenia widely exists in elderly people and triggers numerous age‐related events. The essential pathologic change lies in the increased intramuscular adipose tissue after aging with no exception to non‐obese objects. Pim1 appears to be associated with adipogenic differentiation in recent studies, inspiring us to explore whether it regulates adipogenesis in aging muscles and affects sarcopenia. Methods: Wild‐type and Pim1 knockout C57/BL6J mice were randomized into young and old groups. Histo‐pathological and molecular biological methods were applied to assess the intramuscular adipose tissue content, the atrophy and regeneration, and the expressions of Pim1 and adipogenic transcription factors. PDGFRα + mesenchymal progenitors were separated and their replicative aging model were established. Different time of adipogenic induction and different amounts of Pim1 inhibitor were applied, after which the adipogenic potency were evaluated. The expressions of Pim1 and adipogenic transcription factors were measured through western blotting. Results: The aging mice demonstrated decreased forelimb grip strength ( P = 0.0003), hanging impulse ( P < 0.0001), exhaustive running time ( P < 0.0001), tetanic force ( P = 0.0298), lean mass ( P = 0.0008), and percentage of gastrocnemius weight in body weight ( P < 0.0001), which were improved by Pim1 knockout ( P = 0.0015, P = 0.0222, P < 0.0001, P = 0.0444, P = 0.0004, and P = 0.0003, respectively). To elucidate the mechanisms, analyses showed that Pim1 knockout decreased the fat mass ( P = 0.0005) and reduced the intramuscular adipose tissue content ( P = 0.0008) by inhibiting the C/EBPδ pathway ( P = 0.0067) in aging mice, resulting in increased cross‐sectional area of all and fast muscle fibres ( P = 0.0017 and 0.0024 respectively), decreased levels of MuRF 1 and atrogin 1 ( P = 0.0001 and 0.0329 respectively), and decreased content of Pax7 at the basal state ( P = 0.0055). In vitro, senescent PDGFRα + mesenchymal progenitors showed significantly increased the intracellular adipose tissue content (OD510) compared with young cells after 6 days of adipogenic induction ( P < 0.0001). The Pim1 expression was elevated during adipogenic differentiation, and Pim1 inhibition significantly reduced the OD510 in senescent cells ( P = 0.0040) by inhibiting the C/EBPδ pathway ( P = 0.0047). Conclusions: Pim1 knockout exerted protective effects in sarcopenia by inhibiting the adipogenic differentiation of PDGFRα + mesenchymal progenitors induced by C/EBPδ activation and thus reducing the intramuscular adipose tissue content in aging mice. These results provide a potential target for the treatment of sarcopenia.